Perbandingan Penggunaan Efavirenz dan Nevirapine Terhadap Kolesterol LDL Pasien HIV/AIDS - Anggriani, Yusi; Yunihastuti, Evy; Trisna, Yulia; Rosanti, Ade; Manninda, Reise; Annisa, Rifka (UI Scholars Hub, 2019)
Lipid metabolism disorder is one of common condition among HIV (Human Immunodeficiency Virus)/AIDS (Acquired Immune Deficiency Syndrome) patients who used first line antiretroviral efavirenz and nevirapine. This study was conducted to compare LDL (Low Density Lipoprotein) cholesterol between two group HIV/AIDS patients with efavirenz and nevirapine. The prospective study was performed in 2 months. HIV/AIDS patients who used first line antiretroviral at least for 6 months, aged ≥18 years old, not pregnant, without Mycobacterium ovium complex opportunistic infection and antihyperlipidemic, corticosteroid, retinoid in last 3 months were included. The 70 patients who enrolled in this study were divided into two groups. The independent T test was carried out to analyze the different of LDL cholesterol between two group. The group of patients using efavirenz showed 142.31 ±41,461 mg/dL and the group of nevirapine 126.83 ±40,55 mg/dL LDL cholesterol. This study showed that patient with efavirenze had higher LDL than nevirapine, but not statistically different.